CULTURAL INFLUENCES ON LISTENING COMPREHENSION - Teshaboyeva Nafisa Zubaydulla qizi; Xamidova Mashxura Abror qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Cultural factors significantly impact listening comprehension, influencing how individuals understand spoken language. Cultural background shapes interpretations of idioms, humor, social cues, and contextual references. Familiarity with communication styles (e.g., directness or formality) can enhance or hinder comprehension. Learners may struggle with culturally specific references or accents, making it essential to incorporate cultural literacy in language learning. Cultural competence helps learners navigate language nuances, improving their ability to understand diverse accents and communication styles in real-world contexts.